Hydroxychloroquine Enhances Cytotoxic Properties of Extracellular Vesicles and Extracellular Vesicle–Mimetic Nanovesicles Loaded with Chemotherapeutics - Sergey Brezgin; Anastasiya Kostyusheva; Natalia Ponomareva; Ekaterina Bayurova; Alla Kondrashova; Anastasia Frolova; Olga Slatinskaya; Landysh Fatkhutdinova; Georgy Maksimov; Mikhail Zyuzin; Ilya Gordeychuk; Alexander Lukashev; et al. (Pharmaceutics, 2023)
Because of their high biocompatibility, biological barrier negotiation, and functionalization properties, biological nanoparticles have been actively investigated for many medical applications. Biological nanoparticles, including natural extracellular vesicles (EVs) and synthetic extracellular vesicle–mimetic nanovesicles (EMNVs), represent novel drug delivery vehicles that can accommodate different payloads. In this study, we investigated the physical, biological, and delivery properties of EVs and EMNVs and analyzed their ability to deliver the chemotherapeutic drug doxorubicin. EMNVs and EVs exhibit similar properties, but EMNVs are more effectively internalized, while EVs show higher intracellular doxorubicin release activity. In addition, these nanotherapeutics were investigated in combination with the FDA-approved drug hydroxychloroquine (HCQ). We demonstrate that HCQ-induced lysosome destabilization and could significantly increase nanoparticle internalization, doxorubicin release, and cytotoxicity. Altogether, these data demonstrate that, from the delivery standpoint in vitro, the internalization of EMNVs and EVs and their payload release were slightly different and both nanotherapeutics had comparable cytotoxic performance. However, the synthesis of EMNVs was significantly faster and cost-effective. In addition, we highlight the benefits of combining biological nanoparticles with the lysosome-destabilizing agent HCQ that increased both the internalization and the cytotoxic properties of the particles.